Penafsiran Ayat Tentang Berpakaian (Berhias) - Frandita Juwika; Atikah Yesi Duana Sari; Ridho Wahyudi Siregar; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the concept of dress ethics in Islam, focusing on the dress code for both men and women as well as the ethics that should be applied when dressing. In Islam, dressing is not merely a matter of appearance, but also related to religious teachings that emphasize the importance of covering the aurat, maintaining modesty, and preserving honor. For men, the dress code is strictly regulated by Sharia, including the aurat limitation between the navel and the knee, the prohibition of wearing gold and silk, and the prohibition of imitating women's or non-Muslims' clothing. Meanwhile, for women, the dress code is more complex with specific requirements such as covering the aurat, wearing non-transparent clothing, not accentuating body contours, and avoiding imitation of men's or non-Muslim clothing. This study also highlights the concept of tabarruj, which refers to the act of displaying jewelry and beauty to men who are not mahram, considered a violation of Islamic dress ethics. Additionally, this research explains the meaning of jilbab in the Qur'an, which is understood as an outer garment that covers the entire body, serving as protection and a means of distinguishing believing women. Overall, dress ethics in Islam encompasses not only physical aspects but also spiritual ones, reflecting devotion to Allah through sincere intentions in accordance with religious teachings. This study provides a deeper understanding of the significance of dress ethics as part of a Muslim's identity in faith.